Environmental enrichment during yard weaning alters the performance of calves in an attention bias and a novel object recognition test - Dickson, Emily J.; Monk, Jessica E.; Lee, Caroline; Campbell, Dana L. M. (Frontiers in Animal Science, 2024)
The weaning of beef calves in yards places multiple stressors on the animals, and environmental enrichment may help to mitigate some of these stressors and improve animal welfare. This trial assessed the impacts of enrichment provision to beef calves during yard weaning, using measures of biological functioning, behaviour, and affective state. Overall, calves utilised the brush more than other provided enrichments, which were a hanging rope and a ball. Enrichment influenced the behaviours of calves during both an attention bias test, with enriched calves exhibiting behaviours associated with greater anxiety, and a novel object recognition test, with enriched calves spending less time interacting with objects. In their home pens, enriched calves performed more drinking and grooming behaviours. However, no significant differences were seen between treatments for body weight, faecal cortisol metabolites, and internal body temperature. Enrichment also did not influence any longer-term measurements of body weight, flight speed, or crush score. The study design was impacted by mud, requiring regrouping of the animals, thus some results should be interpreted with caution. Overall, this study demonstrates that further work is required into the assessment of affective states for these animals, as it could not be confirmed if the results seen indicate if calf welfare was improved or impaired through enrichment provision.